2021
DOI: 10.1038/s41467-021-24059-y
|View full text |Cite
|
Sign up to set email alerts
|

Converting copper sulfide to copper with surface sulfur for electrocatalytic alkyne semi-hydrogenation with water

Abstract: Electrocatalytic alkyne semi-hydrogenation to alkenes with water as the hydrogen source using a low-cost noble-metal-free catalyst is highly desirable but challenging because of their over-hydrogenation to undesired alkanes. Here, we propose that an ideal catalyst should have the appropriate binding energy with active atomic hydrogen (H*) from water electrolysis and a weaker adsorption with an alkene, thus promoting alkyne semi-hydrogenation and avoiding over-hydrogenation. So, surface sulfur-doped and -adsorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(67 citation statements)
references
References 66 publications
5
62
0
Order By: Relevance
“…32 ) owing to the strong interaction between Zn and S (refs. 16 , 48 , 49 ), although it mainly produces H 2 (Supplementary Fig. 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…32 ) owing to the strong interaction between Zn and S (refs. 16 , 48 , 49 ), although it mainly produces H 2 (Supplementary Fig. 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…When tetramethylammonium hydroxide (TMAOH) and NaOH are used to replace KOH electrolytes, Pd@ArS-Pd 4 S NTs exhibit lower current density and a sluggish alkyne hydrogenation process under other identical conditions (fig. S14), due to the weaker interaction between S 2− and TMA + and the larger ionic hydration number and radius of the hydrated cation of Na + (H 2 O) n ( n = 7 for K + versus 13 for Na + ) ( 15 ). Consequently, the preliminary results suggest that both the NT structure and the concentrated K + are essential in promoting the electrochemical transfer semihydrogenation of alkynes with water, rationalizing our speculation and theoretical prediction.…”
Section: Resultsmentioning
confidence: 99%
“…Its Faraday efficiencies (FEs) of alkenes are highly dependent on the precise controls on cathodic potentials and reaction time. To address these issues, a low-coordinated copper cathode with surface sulfur (S) was then found that allowed the highly selective synthesis of alkenes across a wide potential range ( 15 ). However, its reaction rate was relatively low because of the weak hydrogenation ability of Cu itself, thus a higher potential is required to drive the semihydrogenation with only 3.6 to 10% FEs due to competitive hydrogen evolution reaction (HER).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the thermocatalytic path, this process is advantageous in being operatable under mild conditions and is environmental-friendly in combination with electroreduction of water based on renewable electricity, in which hydrogen is in-situ generated for the reduction reaction so that extra supply of H 2 can be avoided (Fig. 1 ), which emerges as an attractive route for semihydrogenation of alkynes 13 – 15 . By optimizing the Cu catalyst to expose more active facets, preferential adsorption and hydrogenation of acetylene is facilitated against hydrogen adsorption and evolution.…”
Section: Introductionmentioning
confidence: 99%